The Category of Existential Continuum in the English Biographical References - D. A. Efremova (Vestnik MGIMO-Universiteta)
The article is devoted to the peculiarities of existential continuum in English biographical references, which are investigated in terms of text linguistics and discourse analysis. The text manifestation of the category of the existential continuum has, as a whole, an objective character; however subjectivity is expressed in its individual and author's partitioning of the text, a metaphorisation, figurativeness, anecdotism and the functioning of the categories of time and space as a means of the characters’ characteristics.